2013
DOI: 10.5194/hess-17-225-2013
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, maximum power, and the dynamics of preferential river flow structures at the continental scale

Abstract: Abstract.The organization of drainage basins shows some reproducible phenomena, as exemplified by self-similar fractal river network structures and typical scaling laws, and these have been related to energetic optimization principles, such as minimization of stream power, minimum energy expenditure or maximum "access". Here we describe the organization and dynamics of drainage systems using thermodynamics, focusing on the generation, dissipation and transfer of free energy associated with river flow and sedim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 42 publications
6
124
0
Order By: Relevance
“…Nevertheless, several authors already showed their potential (e.g. Kleidon and Schymanski, 2008;Schymanski et al, 2010;Zehe et al, 2010;Porada et al, 2011;Kleidon et al, 2013), but generally little guidance was given on how to use the principle. For example, Kleidon and Schymanski (2008) set up a simple model to illustrate how MEP could be used to estimate the resistance for root water uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several authors already showed their potential (e.g. Kleidon and Schymanski, 2008;Schymanski et al, 2010;Zehe et al, 2010;Porada et al, 2011;Kleidon et al, 2013), but generally little guidance was given on how to use the principle. For example, Kleidon and Schymanski (2008) set up a simple model to illustrate how MEP could be used to estimate the resistance for root water uptake.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore focused on the average yearly water balance, which we assume to reflect steady state partitioning of rainfall into hydrological fluxes (Kleidon et al, 2013). We used a simple bucket model to which we applied the maximum power principle.…”
Section: Model Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…This limit results fundamentally from the laws of thermodynamics, as shown in the brief derivation in the Appendix A1, and surface exchange fluxes 525 are subjected to this limit. This limit relates very closely to a range of previous applications of thermodynamic limits to similar systems, e.g., to turbulent phenomena (Ozawa et al, 2001), planetary heat transport (Lorenz et al, 2001), to the atmospheric circulation (Kleidon et al, 2003(Kleidon et al, , 2006, and 530 to hydrology (Kleidon and Schymanski, 2008;Zehe et al, 2010;Kleidon et al, 2013;Zehe et al, 2013). While the existence of this thermodynamic limit should hence not be a concern, the question is rather whether land surface fluxes indeed operate at this limit, and whether the assumption of 535 the steady state is justified.…”
mentioning
confidence: 99%
“…In the PUB research program, data acquisition techniques (Hilgersom and Luxemburg, 2012), experimental studies (McMillan et al, 2012;Ali et al, 2012), advanced models and strategies (Harman, 2008), and new hydrological theories (Kleidon et al, 2013) have been developed to improve hydrological prediction results for ungauged zones.…”
mentioning
confidence: 99%